Quantum histories and correlations in quantum measurements - Losada, Marcelo Adrián (2018)
In this paper, the measurement process is described as an interaction between two quantum systems: the system to be measured and the measuring instrument. The time evolution is determined only by the Schrödinger equation, i.e., there is no collapse postulate. The description of the measurement process is performed using the quantum histories approach, which allows to express the correlation between the properties of the measured system, before the measurement, and the properties of the pointer variable of the instrument, after the measurement. From the point of view of this approach, we explore the possibility of obtaining information of incompatible observables with the same instrument, using different families of histories.